SOSIALISASI DAN PELATIHAN BUDIDAYA IKAN KERAPU( Epinephelus sp.) UNTUK MASYARAKAT NELAYAN DESA HAKATUTOBU, KECAMATAN POMALAA, KABUPATEN KOLAKA - Purbaningsih, Yuli; Kurnia, Agus; Pariakan, Arman; Salma, Wa Ode; Nurmaladewi, Nurmaladewi; Asni, Asni; Muis, Muis; Salsabila, Syefira; Rezal, Farit; Hamid, Abdul; Ruslaini, Ruslaini; Nuridah, Nuridah; Haya, Yasir (Universitas Mataram, 2025)
Introduction. Grouper is an economically important marine fish commodity and it is one of the mainstays of Indonesian marine fish exports. Hakatutobu Village is one of the coastal villages in Pomalaa District, Kolaka Regency where the community has carried out grouper cultivation in floating net cages. The results of our preliminary review and interviews with fish farmers in the village found the problem of a lack of knowledge about best grouper cultivation which has a direct impact on fish culture production. Objective. This community service activity aims to increase the knowledge of the fishermen community about grouper cultivation technology which includes seed stocking techniques, feeding management, observing water quality, preventing and handling of fish diseases, monitoring of water quality and proper fish harvesting techniques. Implementation method. Methods for implementing the community service included of location surveys, coordination between the service team (Lecturers at Nineteen November University Kolaka and Halu Oleo University), Cultivating Fishermen and the Head of Hakatutobu Village, outreach activities and socialization and evaluation of activities. Activity Results. The results of this activity were the implementation of training activities and outreach on grouper cultivation, the number of training participants exceeding the number of participants invited, the level of understanding and satisfaction of the community regarding the implementation of the service was high. Conclusion. It is hoped that knowledge and understanding of good grouper cultivation techniques can increase grouper production and become a mainstay commodity for villages, thereby increasing the income and welfare of fish farmers in particular and the Hakatutobu Village community in general.